Treatment Patterns of Patients With Pulmonary Hypertension: A Descriptive Study in Colombia - Manuel Machado‐Duque; Andrés Gaviria‐Mendoza; Luis Fernando Valladales‐Restrepo; Manuel Pacheco; Juan Sebastián Franco; María delRosario Forero; Rubiela Suarez; Oscar Peñuela; Jorge E. Machado‐Alba (The Clinical Respiratory Journal)
ABSTRACT Introduction Pulmonary hypertension (PH) is a chronic disease characterized by a progressive rise in pulmonary artery blood pressure. The objective was to describe the treatment patterns among ambulatory patients with pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH) in a real‐world setting. Methods This is a longitudinal cohort follow‐up study characterizing the treatment patterns of patients diagnosed with PAH or CTEPH, with secondary data from a population‐based drug‐dispensing database between 2022 and 2023, which includes sociodemographic, diagnosis, prescribing specialty, and treatment (drugs, persistence of use, and concomitant medications). Results In total, 1045 patients with a diagnosis of PH were identified, with mean age of 62.9 ± 18.2 years, and 72.3% of females; of which 947 (90.6%) received monotherapy, and 98 (9.4%) received combination therapy at the beginning of follow‐up. The most frequently used drugs for the treatment of PH were calcium channel blockers (58.1%), followed by phosphodiesterase 5 inhibitors (41.1%), endothelin receptor antagonist (32.5%), and guanylate cyclase stimulants (9.7%). The schemes used most frequently were monotherapy with amlodipine (31.0%), sildenafil (19.2%), or nifedipine (10.0%), but the main combination were sildenafil with nifedipine (2.5%). The mean of persistence of use was 161 ± 123 days during 1 year of follow‐up. Conclusions This group of patients with PH from Colombia were treated predominantly with monotherapy of calcium channel blockers and phosphodiesterase 5 inhibitors. However, current clinical practice guidelines recommend the use of combined therapy. The average persistence of the use of drugs for treatment for less than 6 months may be associated with difficulties in follow‐up, adherence, effectiveness, tolerability, and access.